Advanced computational intelligence paradigms in healthcare 5 intelligent decision support systems - Brahnam, Sheryl; Jain, Lakhmi C.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book is a continuation of the previous volumes of our series on Advanced Computational Intelligence Paradigms in Healthcare. The recent advances in computational intelligence paradigms have highlighted the need of intelligent systems in healthcare. This volume provides the reader a glimpse of the current state of the art in intelligent support system design in the field of healthcare. The book reports a sample of recent advances in: Clinical Decision Support Systems Rehabilitation Decision Support Systems Technology Acceptance in Medical Decision Support Systems The book is directed to the researchers, professors, practitioner and students interested to design and develop intelligent decision support systems.
Part 1: Clinical Decision Support Systems -- Part 2: Rehabilitation Decision Support Systems -- Part 3: Technology Acceptance in Medical Decision Support Systems.
Electronic reproduction.
Keywords: Medicine|xData processing; Computational intelligence; Electronic books